Global Face with a National Body? Facebook Appropriation and Use in a National Context - Klastrup, Lisbeth (AoIR Selected Papers of Internet Research, 2013)
This paper presents a study of Facebook in a national context, examining language use, friend networks, and content interaction and sharing. Based on a survey (n=739), four in-depth qualitative interviews with people living in Denmark, and ethnographic observation, the paper present findings which indicate that Danes (of Danish origin) on Facebook mostly interact in Danish with other Danes they know, focusing on their own life and local news, whereas Danes with a mixed background interact with people in several countries, in several languages, and with a more international outlook, but still only with people, they know. A majority share international entertainment (such as YouTube videos), and sign up for international groups and activities on Facebook. However, a minority seem to be living in a Danish capsule. Nothing in these findings indicate strong globalising effects by being on Facebook, but mundane global (sharing) activity needs to be examined further.